Konfigurasi Spasial dan Keterbukaan Visual pada Interior Coffee Shop: Analisis Space Syntax - Rexha Septine Faril Nanda; Kiki Putri Amelia; Hana Faza Surya Rusyda (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Pradita, 2026)
This study is based on the design concept of Sawo Coffee and Roastery, which aims to create a coffee shop that is visually contrasting yet remains contextual to the heritage environment of Braga through visual openness, transitional spaces, and a minimalist interior that provides an inviting and comfortable spatial experience. This strategy is implemented through the use of a transparent facade, a building setback that forms a transitional space for pedestrians, and landscape elements as an entrance path that enhances visual attraction from the pedestrian corridor. This approach reflects a design effort to establish a visual connection between exterior and interior spaces. However, a strategy that emphasizes visual aspects does not necessarily correspond to a spatial configuration that supports optimal spatial connectivity and accessibility. Therefore, this study aims to evaluate the relationship between visual design strategies and spatial configuration using a space syntax approach. The method employed is a quantitative descriptive approach by analyzing connectivity, total depth, mean depth, relative asymmetry, real relative asymmetry, and visual graph analysis (VGA) based on spatial topology representation. The case study focuses on Sawo Coffee and Roastery in Bandung, using architectural plans and visual documentation as the basis of analysis. The results indicate that the initial transitional areas possess high visual visibility based on VGA results, allowing users to visually perceive interior activities from the pedestrian area. However, the space syntax analysis reveals that initial spaces such as the semi-outdoor area (RRA 1.537) and souvenir space (RRA 1.592) have low integration levels and relatively high spatial depth. This condition indicates that visual openness is not fully accompanied by optimal spatial connectivity. Thus, the effectiveness of commercial space design is determined not only by visual transparency, but also by spatial configurations capable of creating stronger integration, clearer orientation, and easier accessibility from the entrance area.